Implementasi Jurnalisme Dakwah dalam Media Online Islam: Analisis Isi Berita VOA-Islam.com - Hakim, Lukman; Meidayanti, Anisah (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2020)
The proliferation of Islamic-based media in the Indonesian post-reform era has made an important contribution in spreading Islamic information and proselytising on the one side, and generate socio-political conflict on the other side. This article reports on research conducted with 2 of those news coverage samples in the online media of VOA. Islam .com, using a quantitative descriptive of content analysis. Findings illustrated a poor implementation of da’wah journalism elements which adapted from common journalism principles such as honesty, fairness, impartiality, and accuracy of information. However, these Islamic-based online news sites indicated greater attention to implement da’wah journalism characteristics based on Islamic values regarding how information should be conveyed to audiences such as Qaulan Ma’rufan, Qaulan Kariman, Qaulan Masyuran, Qaulan Balighan, and Qaulan Layyinan.